Osthole Blocks HMGB1 Release From the Nucleus and Confers Protective Effects Against Renal Ischemia-Reperfusion Injury - Dai, Qing; Xie, Deqiong; Zhang, Chenli; Zhu, Lei; Xu, Ying; Li, Kui; Hao, Wen; Yin, Hefei (Frontiers in Physiology, 2021)
Renal ischemia-reperfusion (IR) is one of the main causes of renal injury. In severe cases with serious consequences, IR-related renal damage progresses rapidly and can even lead to acute renal failure. Its clinical treatment is currently difficult. According to various studies at home and abroad, HMGB1 is released from the nucleus into the cytoplasm or extracellular space by damaged parenchymal cells during ischemia and hypoxia, and this plays an important role in the initiation of reperfusion injury as an early inflammatory factor and is closely related to the occurrence and development of renal diseases. In recent years, the protective effect of osthole on IR of tissues and organs has been a key topic among clinical researchers. Osthole can inhibit the inflammatory response, reduce cell apoptosis the progression, and improve the prognosis of IR, thus protecting the kidney. During the development of renal IR, finding a mechanism through which the osthole blocks the release of HMGB1 from the nucleus would be helpful in detecting targets for clinical treatment.